Phylogenetic Investigations on Ten Genera of Tintinnid Ciliates (Ciliophora: Spirotrichea: Tintinnida), Based on Small Subunit Ribosomal RNA Gene Sequences. (24th January 2013) - Xu, Dapeng; Sun, Ping; Warren, Alan; Hoon Noh, Jae; Lim Choi, Dong; Kyoon Shin, Mann; Ok Kim, Young
Abstract Tintinnida is a diverse taxon that accommodates over 1, 500 morphospecies, which is an important component of marine planktonic food webs. However, evolutionary relationships of tintinnids are poorly known because molecular data of most groups within this order are lacking. In our study, the small subunit (SSU) rRNA genes representing 10 genera, 5 families of Tintinnida were sequenced, including the first SSU rRNA gene sequences for Coxliella, Dadayiella, Epiplocyloides, and Protorhabdonella, and phylogenetic trees were constructed to assess their intergeneric relationships. Phylogenies inferred from different methods showed that (1) Three newly sequenced Eutintinnus species fell into Eutintinnus clade forming a sister group to the clade containing Amphorides, Steenstrupiella, Amphorellopsis, and Salpingella; (2) Surprisingly, the genetic distances between Amphorides amphora and Amphorellopsis acuta population 1 was even smaller than that between the two populations of Amphorellopsis acuta, casting doubt on the validity of Amphorides and Amphorellopsis as presently defined; (3) The SSU rRNA sequences of Dadayiella ganymedes and Parundella aculeata were almost identical. Therefore, Parundella ganymedes novel combination is proposed; (4) Coxliella, which is currently assigned within Metacylididae, branched instead with some Tintinnopsis species. Furthermore, the validation of Coxliella, which was considered to be a "questionable" genus, was confirmed based on evidences from morphology, ecology, and molecular data; (5) Protorhabdonella and Rhabdonella showed rather low intergeneric distance and grouped together with strong support suggesting that Rhabdonellidae is a well‐defined taxon; and (6) Epiplocyloides branched with species in Cyttarocylididae indicating their close relationship.